The differences of body measurements in captive Sumatran elephant on different captivity management and sex - DENY SETYO WIBOWO; ALEK IBRAHIM; RINI WIDAYANTI; WISNU NURCAHYO; MUHAMMAD WAHYU; JOHAN R. MICHAUX; HERY WIJAYANTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wibowo DS, Ibrahim A, Widayanti R, Nurcahyo W, Wahyu M, Michaux J, Wijayanto H. 2021. The differences of body measurements in captive Sumatran elephant on different captivity management and sex. Biodiversitas 22: 2619-2624. Sumatran elephants are one of wild animals in Indonesia that currently received critically endangered status. This study aimed to measure the body size of both sexes of Sumatran elephants in the semi-captive (ECCs) and full captive (Zoo) management for conservation purposes. This study was conducted in ECCs in Sumatran island and Zoo on Java island. Body measurements (Chest Girth, Length, Height, Tarsal and Carpal Circumference) were collected from a total of 49 samples of captive Sumatran elephants (25 from EECs and 24 from Zoo). Data were analyzed using a completely randomized factorial design with different management and sex as the factors. The results showed that BL (304.92 vs 311.13) and TC (76.44 vs 77.50) were significantly different (P<0.05) across captivity managements. Sex categories (male and female) showed significant results (P<0.01) on CG (321.71 vs 302.46), BL (303.50 vs 272.49), BH (230.14 vs 208.23) and TC (82.29 vs 74.83). No interaction was identified between captive management and sex on body measurements. In conclusion, there were significant differences in body size of male and female elephants. This result contributed well-researched information to evaluate the conservation management based on body size and for further research on Sumatran elephant conservation.